Peran Pemerintah Kabupaten Malang dalam Meningkatkan Pembangunan Ekonomi Daerah melalui Sektor Pariwisata - Theresia Octastefani; Bayu Mitra Adhyatma Kusuma (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
This study aims to analyze and describe the role of Malang Regency Government in improving the local economic development through the tourism sector, in this case Balekambang Beach particularly. To analyze this problem, the researchers used the perspective of the New Public Management. This research uses qualitative type of research, descriptive analysis approach, and the interactive data analysis methods of Miles and Huberman. The research results showed that in improving the local economic development through the tourism sector, Malang Regency Government has to play its role as an entrepreneur, coordinator, facilitator, and stimulator with as much as possible to be able to boost regional economic development. Despite in the fact cannot be denied that there are still obstacles or barriers that must be faced in playing the role of the government.